How Loyal Are Consumers To Online Transportation In East Java ? - Dian Permata Sari; Fahrurrozi; Addainuri, Muhammad Isbad (Paradoks : Jurnal Ilmu Ekonomi, 2025)
The increase in the use of online transportation in East Java cannot be separated from the role of social media as a means of promotion and interaction with consumers. Consumers are now more inclined to choose transportation services not only because of price, but also because of their trust in the brand and the quality of the digital experience offered. This study attempts to analyze the factors that influence consumer loyalty to online transportation services, with a focus on the role of social media marketing, brand trust, brand affect, and value consciousness. In addition, brand trust is also tested as a mediating variable that connects social media marketing with brand loyalty. This study uses a quantitative approach involving 311 respondents who are online transportation users in East Java through purposive sampling. Data was obtained using a Likert scale-based questionnaire and analyzed using SEM-PLS version 4.0. The results show that social media marketing and brand trust have a positive and significant effect on brand loyalty, while brand affect and value consciousness do not have a significant effect. Social media marketing is also proven to increase brand trust, which then mediates the relationship with brand loyalty. These findings confirm that in the online transportation industry, consumer trust is the main factor in shaping loyalty, while emotional aspects and price awareness are not as decisive. This research can serve as a theoretical reference for the development of digital marketing and brand loyalty literature, as well as a practical guide for online transportation companies to focus more on building brand trust through transparent, interactive, and consistent social media marketing strategies in order to strengthen consumer loyalty.